MICROKINETIC STUDY OF METHANOL SYNTHESIS FROM CO2 AND CO HYDROGENATION ON NICKEL-BASED CATALYST - Luthﬁ Maulana (13314044), Refaldi Intri Dwi Putra (13314072), Ariﬁn
Methanol (CH3OH) synthesis through syngas (a gas mixture of CO2, CO, and H2) hydrogenation on Cu-based catalyst has been used for quite a long time by industry and has been inspected thouroughly to be developed as well. A research for methanol synthesis via CO2 and CO hydrogenation over nickel-based catalyst has been accomplished through this study. The eﬀect of dopant introduction to nickel surface was investigated by substituting one Ni atom on Ni(111) surface with Cu, Pd, Pt, or Rh. This action showed satisfying result where CO2 hydrogenation reaction via CO2-H2COO* pathway was accelerated in respect to pure Ni catalyst. Hydrogenation reaction on Ni-Cu catalyst appeared to have the best TOF (3.12 x 10-6 site-1 s-1) on T = 573 K and P = 75 bar compared to other catalyst. On CO hydrogenation pathway, Ni-Rh catalyst displayed promising result both in HCO* and COH* intermediate pathway. A manipulation of external variable disclosed a quite signiﬁcant increase in TOF when the temperature is raised, the pressure is decreased, and the composition of H2 gas in syngas feed is increased. A reaction which describe the whole methanol synthesis process for each pathway has been found using PearsonÃ‚Â’s correlation of activation energyÃ‚Â–reaction energy and BEP correlation.